Downward spectral solar radiance as measured in different depths under sea ice (transmitted radiance) at station PS122/3_34-20 on 2020-03-31 - Nicolaus, Marcel; Anhaus, Philipp; Arndt, Stefanie; Katlein, Christian; Krampe, Daniela; Lange, Benjamin Allen; Matero, Ilkka; Regnery, Julia; Rohde, Jan; Schiller, Martin (In: Nicolaus, M et al. (2021): Spectral solar radiation over and under sea ice during the MOSAiC campaign 2019/20 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.935688, 2022)
Downward spectral solar radiance as measured in different depths under sea ice (transmitted radiance). The radiance sensor (7° opening) was installed on the ROV.
Keywords: Mosaic; Radiation fluxes; ROV remotely operated vehicle; Sea ice